LEGAL FOUNDATIONS OF THE ART MARKET AND ITS ROLE IN THE CREATIVE INDUSTRY (European Journal of Interdisciplinary Research and Development, 2025)
The article analyzes the legal foundations of the art market and their role in the development of creative industries. It examines key normative legal acts and state programs adopted in recent years that have shaped the institutional and legal framework of the modern art market. Special attention is paid to the influence of the art sector on the creative economy, its capital-intensive nature, and the formation of new legal mechanisms for regulating the circulation of cultural and artistic values. The paper highlights the importance of legal regulation in ensuring the transparency, accessibility, and investment attractiveness of the art market within the system of creative industries.